MHD flow of an elastico-viscous fluid under periodic body acceleration - E. F. El-Shehawey; Elsayed M. E. Elbarbary; N. A. S. Afifi; Mostafa Elshahed (International Journal of Mathematics and Mathematical Sciences)
Magnetohydrodynamic (MHD) flow of blood has been studied under the influence of body acceleration. With the help of Laplace and finite Hankel transforms, an exact solution is obtained for the unsteady flow of blood as an electrical conducting, incompressible and elastico-viscous fluid in the presence of a magnetic field acting along the radius of the pipe. Analytical expressions for axial velocity, fluid acceleration and flow rate has been obtained.